SUMOylation in Skeletal Development, Homeostasis, and Disease - Huadie Liu; Sonya E. L. Craig; Vladimir Molchanov; Joseph S. Floramo; Yaguang Zhao; Tao Yang (Cells, 2022)
The modification of proteins by small ubiquitin-related modifier (SUMO) molecules, SUMOylation, is a key post-translational modification involved in a variety of biological processes, such as chromosome organization, DNA replication and repair, transcription, nuclear transport, and cell signaling transduction. In recent years, emerging evidence has shown that SUMOylation regulates the development and homeostasis of the skeletal system, with its dysregulation causing skeletal diseases, suggesting that SUMOylation pathways may serve as a promising therapeutic target. In this review, we summarize the current understanding of the molecular mechanisms by which SUMOylation pathways regulate skeletal cells in physiological and disease contexts.